(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The industrial sector is one of the vital sectors that contributes to the country’s economic growth. There is increasing attention towards project management to serve the diverse demands of the customers and for sustainable industrial growth. One of the fundamental knowledge areas in project management is “Risk Management (RM).” For leveraging performance and ensuring sustainable growth, identification of critical risks and effective RM implementation is of utmost importance. However, in today’s survival of the fittest industrial techno-economic scenario, despite the known field, RM has not got full attention, especially in the context of Small and Medium Enterprises (SME’s) across sectors. Traditionally risk is analyzed in the context of finance and safety only. For sustainable growth, equal focus on risk assessment and RM in other aspects is of paramount importance. This paper seeks to explore the Critical Risk Factors (CRFs) along with barriers for RM implementation in construction, manufacturing, and software industries by an in-depth review of 44 published articles. The paper presents various tools/techniques applied by researchers, enlists risk factors within the sector, and reveals challenges or barriers for RM implementation in a specific context. This article provides valuable insights into the RM domain by unfolding critical areas of concern for developing proactive risk mitigation strategies and way forward to future research conduct.